1981
DOI: 10.1002/ajmg.1320090108
|View full text |Cite
|
Sign up to set email alerts
|

Historical note: The extraordinary handless and footless families of Brazil – 50 years of acheiropodia

Abstract: The history of acheiropodia is divided into 4 phases: discovery, exploration, modern studies, and contemporary knowledge. The discovery phase (1929-1930) is represented by the publication of the 1st family. For about 30 years, it remained the only family referred to in a number of textbooks of medicine, biology, and others. In the exploration phase (1956-1966), the first family was reanalyzed, other families were ascertained and analysed, and some radiologic aspects of the anomaly were published. The modern ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…No se han descrito otras anomalías congénitas. 1 L a e n f e r m e d a d s e h a o b s e r v a d o e n individuos de uno y otro sexo y no se ha descrito la transmisión de padres a hijos. Estos datos, sumados a la presencia de consanguinidad parental en varias de las familias, indican un patrón de herencia autosómico recesivo.…”
Section: Caso Clínicounclassified
See 1 more Smart Citation
“…No se han descrito otras anomalías congénitas. 1 L a e n f e r m e d a d s e h a o b s e r v a d o e n individuos de uno y otro sexo y no se ha descrito la transmisión de padres a hijos. Estos datos, sumados a la presencia de consanguinidad parental en varias de las familias, indican un patrón de herencia autosómico recesivo.…”
Section: Caso Clínicounclassified
“…La aqueiropodia afecta solo los miembros, y no se ha presentado anomalía de otros órganos o alteraciones cognitivas. 1 Esta enfermedad ha sido descrita principalmente en familias oriundas de Brasil. La incidencia estimada en ese país es de 1 de 250 000 recién nacidos vivos.…”
Section: Introductionunclassified
“…Furthermore, geographic clusters of some single gene diseases in Brazil have been known about for many decades. The pioneer publications include the studies of new mutations for Grebe’s achondrogenesis (OMIM #200700) in the state of Bahia (Quelce-Salgado, 1964); acheiropodia (OMIM #200500) in the state of Minas Gerais (Freire-Maia, 1975, 1981); and oculo-cutaneous albinism (OMIM #203200) in Ilha dos Lençóis (Freire-Maia et al , 1978). Nevertheless, no systematic survey of genetically isolated populations, and/or geographic clusters of genetic disorders, has ever been performed in Brazil on a nationwide level.…”
Section: Introductionmentioning
confidence: 99%
“…As far as I am aware, such a combination of defects is not a recognized syndrome. The absence of hands, feet, forearms, elbows, and lower left leg are compatible with a diagnosis of acheiropodia [Beighton, 1988;Freire-Maia, 1981;Freire-Maia et al, 19781. Acheiropodia is an extremely rare autosomal recessive condition [Freire-Maia et al, 19751 which, to date, has only been identified in Brazilian families of Portuguese descent [Freire-Maia, 19811.…”
Section: Introductionmentioning
confidence: 99%